ANALYSIS OF THE MAIN INDICATORS OF FREIGHT AND TRAIN TRANSPORTATION AT THE “KARSHI” STATION (Modern education and development, 2025)
This article provides a detailed analysis of the freight and train transportation performance of the Karshi railway station in recent years. Based on these analyses, it was noted that there were delays in several directions at the station. In this regard, it was determined that there is a need to improve the station's work processes. To solve these problems, a multi-criteria regression mathematical model of the station's turnaround time was developed. According to it, it was determined that the turnaround time depends on the length of the loading and unloading front, the speed of loading and unloading, and the volume of work at the stations.